Effect of the Buteyko Breathing Technique on Quality of Life Among Adults With Asthma: A Quasi-Experimental Study - Damon Wicaksi; Arif Eko Trilianto; Siska Puspitasari (Fakultas Kesehatan, Universitas Nurul Jadid, 2026)
Background: Asthma is a chronic respiratory disease that can reduce physical function, psychological well-being, social participation, and overall quality of life. In addition to pharmacological therapy, non-pharmacological interventions such as breathing exercises may support asthma self-management. The Buteyko breathing technique is a simple breathing retraining method that may help improve breathing control and quality of life among people with asthma.Objective: This study aimed to examine the effect of the Buteyko breathing technique on quality of life among adults with asthma in Desa Suling Wetan, Kecamatan Cermee, Kabupaten Bondowoso.Methods: This study used a quantitative quasi-experimental design with a pretest–posttest control group approach. A total of 20 adults with asthma were selected using purposive sampling and divided into an intervention group and a control group, with 10 respondents in each group. The intervention group received the Buteyko breathing technique, while the control group did not receive the intervention. Quality of life was measured using a questionnaire, and data were analysed using the Mann–Whitney U test.Results: The mean quality of life score was higher in the intervention group after receiving the Buteyko breathing technique than in the control group, with mean scores of 63.10 and 52.60, respectively. The intervention group also had a higher mean rank than the control group, with mean ranks of 13.35 and 7.65, respectively. The Mann–Whitney U test showed a significant difference in quality of life between the two groups (Z = -2.159; p = 0.031).Conclusion: The Buteyko breathing technique had a significant effect on improving quality of life among adults with asthma. This technique may be considered a simple, low-cost, and non-invasive complementary nursing intervention to support asthma self-management in community settings.